SBIRT TRAINING FOR STUDENT NURSES: HOW AGE, ATTITUDES, AND BELIEFS INFLUENCE PROFICIENCY. (11th November 2018) - Brennan, K; Brossoie, N; Stephen Premo, J; Evan Thomas, M
Abstract: Using a mixed method approach, outcome data from a two-year SAMHSA-funded project to embed the SBIRT approach into the curriculum of a BSN program, is presented. One hundred students were provided online and didactic training, and multiple supervised practice opportunities including a home health clinical simulation with an older male patient. SBIRT proficiency data indicated student reticence to address obvious alcohol use by the standardized patient in the home health scenario. Similarly, anecdotal evidence provided by the standardized patient and nursing faculty suggested student discomfort with addressing alcohol misuse with the elder. Student belief that substance misuse is a form of wrong-doing predicted SBIRT proficiency score rather than acquired knowledge and skills. However, correlations among SBIRT proficiency scores, age, personal attitudes and beliefs about substance misuse and misusers may explain reluctance to talk about alcohol misuse. Implications include rethinking undergraduate curriculum content to include self-examination of personal beliefs and perceptions.